Perempuan dalam Seni Pertunjukan Tari Kelompok â€œSahitaâ€ - Dewi Kristiyanti (Greget, 2009)
â€œSahitaâ€ first appeared in 2001, and is a group of activists who work on womenâ€™s issues. Sahita has to date succeeded in creating six dances, namely Srimpi Srimpet, Srimpi Ketawang Lima Ganep, Iber-iber Tledek Barangan, Pangkur Brujul, Seba Sewaka, and Gathik Glindhing. These works are viewed by the community as the reformation of womenâ€™s roles in a broader life context. The dancersâ€™ movements originate from traditional Javanese dances, and are performed with free, natural, and expressive movements which reflect womenâ€™s struggle to attain gender equality.Keywords: Womenâ€™s concept, dance performance, and friendship.